Speed Limit Enforcement and Road Safety - Stefan Bauernschuster; Ramona Rekers (Institute of Labor Economics (IZA), 2019)
We study the impact on road safety of one-day massive speed limit monitoring operations (SLMO) accompanied by media campaigns that announce the SLMO and provide information on the dangers of speeding. Using register data on the universe of police reported accidents in a generalized difference-in-differences approach, we find that SLMO reduce traffic accidents and casualties by eight percent. Yet, immediately after the SLMO day, all effects vanish. Further evidence suggests that people drive more slowly and responsibly on SLMO days to avoid fines; providing information on the dangers of speeding does not alter driving behavior in a more sustainable way.
Keywords: H76; K42; R41; 330; traffic; law enforcement; safety; accidents